Crisis Information Seeking and Sharing (CISS): Scale Development for Measuring Publics’ Communicative Behavior in Social-Mediated Public Health Crises (Journal of International Crisis and Risk Communication Research, 2019)
This study fi rst refi nes the conceptual framework of publics’ communicative behavior in socialmediated health crises. Then two multiple-item scales for measuring publics’ health crisis information seeking and sharing (CISS) are developed and tested by employing online survey data sets from a random national sample of 279 adults and 280 adults in the United States, respectively. Results indicate seven types of crisis information seeking behavior and 17 types of crisis information sharing behavior crossing over platforms, channels, and information sources. The CISS scales provide a valid and reliable tool for crisis communication researchers and practitioners to measure publics’ information seeking and sharing activities in social-mediated public health crisis communication.